Developing an Interprofessional Student-Led Clinic to Address Health Disparities in a Pacific Islander Migrant Community - McElfish, Pearl Anna; Hudson, Jonell; Schulz, Thomas K; Warmack, Thomas S; Moore, Ramey; Purvis, Rachel S; Dalke, Matthew; Buron, Bill (Journal of Student-Run Clinics, 2017)
Student-led free clinics (SLFC) have become a way to provide care to vulnerable, uninsured populations. SLFCs can offer the opportunity to integrate interprofessional education models emphasizing the roles of different health care disciplines with hands-on learning experiences for students. In 2013, the University of Arkansas for Medical Sciences Northwest established the North Street Clinic, an interprofessional SLFC, in an effort to address the health disparities of the local Marshallese community. This article describes the establishment of the clinic and highlights its core features, such as its unique patient population, interprofessional care teams, use of community health workers, chronic disease management, community partnerships, and use of technology. The North Street Clinic can serve as a model for other SLFCs seeking to integrate IPE into a free care model focused on meeting the chronic disease disparities of an underserved population.